Enhancing Older People's Outdoor Activities Through User-Centered (Shopping Bag) Product Design; A Qualitative Study Based on the User-Centered Approach - Maliheh Naeimi; Parvin Shokri; Robab Sahaf; Hamid Reza Mokhtarinia (University of Social Welfare & Rehabilitation Sciences, 2015)
Objectives The elderly population comprises a large portion of the world's population. The physical constraints faced by this group affect mental and social aspects of their life. Designing and creating new methods may be a solution to a more active contribution in the community. We aimed to study the elderly's social activities and related problems by concentration on their outdoor activities and their result and suggest a product improve them.   Methods & Materials This qualitative study was based on the user-centered approach. Data were collected using questionnaires, observation, interviews and documentation of the participants’ feedbacks. The elderly were selected using. The study was conducted in four stages. First, the questionnaires were distributed among 42 patients. Then 19 seniors (12 women, 7 men) were interviewed. Then their feedback and ideas were documented. Finally, satisfaction was surveyed as the final phase to check the suggested product. Based on their ideas and also studying related and similar samples, data were collected and practical solutions were proposed. Results In the first phase the participants mentioned shopping as their most significant outdoor activity followed by exploring their favorite places for shopping which were fruit and vegetable markets. The problems related to shopping bags were explored through interviews. We found that the elderly need a product to simplify the shopping process of daily goods in order to improve their social activity. An adjustable, safe and stagnate product can increase the satisfaction and also reduce dependence on others in the elderly.  Conclusion Considering the elderly's problems in shopping, a solution in product design is proposed to facilitate shopping and prevent difficulties such as forgetfulness. In future studies considering the anthropometrical measures to adjust the proposed solutions with the specific needs of users is suggested.